The Role of the Social Service for Women’s Empowerment and Child Protection in Overcoming the Phenomenon of Early Marrige (Case Study of Rokan Hulu District) - Buana, Dira; Askarial (Sisi Lain Realita, 2023)
Child marriage has been an issue in Indonesia for a long time. Early marriage brings various impacts on children as they are not yet mature physically or psychologically. This study aims to determine the role of the Social Service for Women's Empowerment and Child Protection in Rokan Hulu Regency in reducing child marriage. This research employs qualitative methods with data collection techniques through interviews and observations. The informants in this study include the head of the agency, department heads, counselors, and early marriage couples. The results show that the Social Service for Women's Empowerment and Child Protection in Rokan Hulu Regency plays a significant role through various initiatives and programs focusing on women's empowerment and child protection. Several programs have been created to reduce the rate of early marriage in Rokan Hulu Regency. The UPTD PPA of this agency focuses on all issues related to children and women. The community has welcomed these programs and hopes they will continue in the long term. Based on the Crime Prevention Theory through a social approach, the role of this agency is quite substantial due to the various strategies implemented by individuals, communities, companies, NGOs, and all levels of government organizations. These efforts target various social and environmental factors that increase the risk of crime, disorder, and victimization, demonstrating that these programs can reduce the rate of early marriage in Rokan Hulu Regency.